Communication and Collaboration Between Pre-School Teachers and Parents (a Case Study of Kaunas City) - Gustaitienė, Indrė; Širiakovienė, Asta (Jaunųjų mokslininkų darbai, 2020)
Collaboration between the family and education staff is a prerequisite for the child’s successful development, but parental engagement in school life is not an easy task. There is a tendency among parents to devote less and less time to communication with teachers, although children’s learning difficulties, poor performance, behaviour problems, etc., are often identified as a consequence of poor parent-teacher collaboration. The aim of this research was to analyze communication and collaboration issues between pre-school teachers and parents. The research was carried out in November 2019 in 8 pre-school education institutions in Kaunas. Respondents were selected using convenience sampling. 50 parents of pre-school age children and 46 teachers took part in the research. Research findings revieled the main barrier to building successful teacher-parent partnerships is that working parents are suffering from work overload and are unwilling to get involved in school activities. Because parents lack time and feel overloaded they do not get involved in activities. Teachers are reluctant to communicate with parents on the phone explaining that it is not easy to fit calls to parents into their day-to-day activities though this form of communication is acceptable and convenient for parents. Teachers and parents alike value time spent communicating and interacting, thus their communication becomes difficult and insincere. No close relationship between teachers and parents arising from common activities was identified. The issue of parent-teacher communication and collaboration is critical since teachers interact with parents only when they bring and collect children and at parents’ meetings, which are seldom held.